UNRAVELING JUSTICE: THE EVOLVING LANDSCAPE OF CRIMINAL LAW IN THE MODERN ERA: UNRAVELING JUSTICE: THE EVOLVING LANDSCAPE OF CRIMINAL LAW IN THE MODERN ERA - Jayawibawa, Marcellus Hakeng (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
This study investigates the evolution of criminal law in Indonesia, focusing on the impact of technological advancements, social shifts, and political changes on the justice system. Utilizing a qualitative research design, including in-depth interviews with legal experts and practitioners, as well as comprehensive document analysis, the research reveals significant trends and patterns in recent legal reforms. Findings indicate that the introduction of procedural standards, such as those outlined in Regulation No. 6 of 2019, has enhanced the transparency and efficiency of criminal investigations. Additionally, the shift towards rehabilitative and restorative justice approaches reflects changing societal attitudes towards crime and punishment. However, challenges persist in fully implementing these reforms and integrating technological advancements into existing legal frameworks. The study concludes that while these reforms contribute positively to the justice system, further research is needed to assess their long-term impacts and practical applications. Recommendations for future research include examining the effectiveness of restorative justice practices and the integration of emerging technologies. For legal practitioners, adapting to these changes and incorporating new technologies and rehabilitative approaches into legal practice are crucial for improving justice outcomes. This research provides valuable insights into the ongoing transformation of criminal law and offers guidance for both scholarly inquiry and practical application in the field of criminal justice.